Abnormal dynamic changes in β-tubulin in somatic nuclear transfer cloned mouse embryos. Issue 1 (February 2015) - Shen, Jingling; Wang, Zhendong; Shen, Xinghui; Zheng, Zhong; Zhang, Qinghua; Feng, Xiuqing; Hu, Lili; Lei, Lei
Summary The efficiency of somatic cell nuclear transfer (SCNT) cloning remains low, thus limiting the applications of this technique. In this study, we used immunochemistry and confocal microscopy to detect the microtubule component, β-tubulin, in SCNT, parthenogenetic (PA), and intracytoplasmic sperm injection (ICSI) embryos before the first mitotic division. β-Tubulin is the component subunit of microtubule, which plays critical roles in regulating localization of cellular organelles, and the growth, maturation and fertilization of oocytes. Our results demonstrated similar changes of spindle patterns in PA and ICSI embryos. The second meiotic division resumed 1 h post-treatment, and the cytoplasmic asters (CAs) disappeared. After about 4–6 h of treatment, pronuclei formed with the midbodies connecting each other. Meanwhile, the CAs reappeared and a microtubule network developed in the cytoplasm. However, SCNT embryos showed abnormal multipolar spindles, and the pseudopronuclei that contained many nucleoli existed after 6 h of SrCl2 activation. Enucleated oocytes alone did not form spindle-like structures when they were artificially activated for 6 h, indicating that somatic cell chromosomes might be necessary for spindle formation in SCNT embryos. These results demonstrated abnormal changes of β-tubulin in mouse SCNT embryos, compared with PA and ICSI embryos.